A showy new Platystele(Pleurothallidinae: Orchidaceae) from northwest Ecuador - Jost, Lou; Iturralde, Gabriel (Lankesteriana: International Journal on Orchidology, 2017)
A new species of Platystele (Pleurothallidinae: Orchidaceae) is described from foothill forest in the province of Carchi in northwestern Ecuador. The species has relatively large flowers for the genus, with long slender sepaline tails. It resembles Platystele caudatisepala, but is distinguished from that species by the partially connate lateral sepals, the convex lip with reflexed tip and margins, the deflexed petals, sometimes with their tips touching behind the flower, the sepals with recurved margins, and the leaves long-petiolate.